1984
DOI: 10.1115/1.3239563
|View full text |Cite
|
Sign up to set email alerts
|

A Summary of Developments of the Mean-Streamline Method in China

Abstract: The mean-streamline method (MSLM) proposed by Wu more than 30 years ago has been further developed in many ways in China since the fifties. Major progress in this method is summarized here. This progress includes: a completely analytical solution of the inverse problem which is extremely quick and more accurate than the original solution, the extension of MSLM to the axisymmetrical flow channels, the extension of the calculation range to transonic flow and nonisentropic flow, the estimation of applicable limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…A survey of this development before 1984 has been presented by Cai [34]. Recent research includes Cai's paper [35] and Wang's paper [36].…”
Section: ) the Mean-streamline Methods (Mslm)mentioning
confidence: 98%
“…A survey of this development before 1984 has been presented by Cai [34]. Recent research includes Cai's paper [35] and Wang's paper [36].…”
Section: ) the Mean-streamline Methods (Mslm)mentioning
confidence: 98%
“…Fig.11 Midspan blade-to-blade surface in 3-D space (SPBC). As mentioned previously a theoretical analysis for twist of blade-to-blade surface in 3-D turbomachinery flow was performed by Cai (1984). It was indicated that in compressor guidevane with non-free vortex design, blade-to-blade surface will twist towards outer periphery (tip) at pressure side of blade, and the order of magnitude of relative twist Lr/r is 10 -2 .…”
Section: Downstream Vsbc and A Simplified Methods Of Solutionmentioning
confidence: 99%
“…3-D flowfield used for the initial estimate of potential is generated by a second-order mean-streamline-method (Cai, 1984) in order to reduce the initial residual. The convergence is assumed to occur when the maximum residual of the governing difference equation (7) does not exceed lx10 5 .…”
Section: Downstream Vsbc and A Simplified Methods Of Solutionmentioning
confidence: 99%
“…(9,10) and recent improvement Ref. (11)(12)(13) ). The solution thus obtained is called quasi-3D solution…”
Section: Abstract a Jacobian Composed Of A•• Bmentioning
confidence: 99%